Adjustment method of deterministic control rods worth computation based on measurements and auxiliary Monte Carlo runs. (November 2015) - Wang, Guan-bo; Ma, Ji-min; Yuan, Shu; Li, Run-dong; Qian, Da-zhi
Highlights: 3-group cross sections is collapsed by WIMS and SN2. Core is calculated by CITATION. Engineering adjustments are made to generate better few group cross-sections. Validation is made by JRR-3M measurements and Monte Carlo simulation. Abstract: The control rods (CRs) worth is key parameter for the research reactors (RRs) operation and utilization. Control rods worth computation is a challenge for the full deterministic calculation methodology, including the few group cross section generation, and the core analysis. The purpose of this work is to interpret our codes system, and their applicability of obtaining reliable CRs worth by some engineering adjustments. Cross sections collapsing in three energy groups is made by WIMS and SN2 codes, while the core analysis is performed by CITATION. We use these codes for the design, construction, and operation of our research reactor CMRR (China Mianyang Research Reactor). However, due to the intrinsic deficiency of the diffusion theory and homogenizing approximation, the directly obtained results, such as CRs worth and neutron flux distributions are not satisfactory. So two points of simple adjustments are made to generate the few group cross-sections with the assistance of measurements and auxiliary Monte Carlo runs. The first step is to adjust the fuel cross sections by changing properly the mass of a non-fissile material, such as the mass of the two 0.4 mm Cd wires existing at both sides of each uranium plate, so that the core model of CITATION can get good eigenvalue when all CRs are completely extracted. The second step is to revise the shim absorber cross section of CRs by adjusting the hafnium mass, so that the CITATION model can get correct critical rods position. In this manuscript, the JRR-3M (Japan Research Reactor No. 3 Modified) reactor is employed as a demonstration. Final revised results are validated with the stochastic simulation and experimental measurement values, including the critical rods position, the differential/integral CR curves, and the thermal neutron flux distributions.